PENGARUH PROMOSI JABATAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BANK SYARIAH INDONESIA KC BATURAJA RAHMAN HAMIDI - Novegya Ratih Primandari; Dyah Ayu Putriani; Dinna Dwi Wahyuni (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study discussed the Influence of Position Promotion and Work Discipline on Employees'Work Productivity at PT. Bank Syariah Indonesia (BSI) KC Baturaja Rahman Hamidi. The data collection technique used in this study was through the distribution of questionnaires. The total population was 30 people. The analytical method used was multiple linear regression. The results showed that partially Job Promotion had a significant influence on Employees'Work Productivity at PT. Bank Syariah Indonesia (BSI) KC Baturaja Rahman Hamidi. For the Work Discipline variable had a significant influence on Employees' Work Productivity at PT. Indonesian Islamic Bank (BSI) KC Baturaja Rahman Hamidi. All X variables, namely Position Promotion (X1) and Work Discipline (X2) jointly had a significant influence on Employees' Work Productivity At PT. Bank Syariah Indonesia (BSI) KC Baturaja Rahman Hamidi. The value of the coefficient of determination (R Square) was 0.796, this indicated that 79.6% was the contribution of Employees'Productivity at PT. Bank Syariah Indonesia (BSI) KC Baturaja Rahman Hamidi could be explained by the variables of Job Promotion (X1) and Work Discipline (X2), while the remaining 20.4% were influenced by variables other than the variables in this study, for example competence (wages or salaries, incentives, rewards and benefits), empowering human resources, and others.